2018
DOI: 10.1016/s0140-6736(17)33108-2
|View full text |Cite
|
Sign up to set email alerts
|

Acalabrutinib in relapsed or refractory mantle cell lymphoma (ACE-LY-004): a single-arm, multicentre, phase 2 trial

Abstract: Acerta Pharma, a member of the AstraZeneca Group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
238
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 353 publications
(260 citation statements)
references
References 23 publications
16
238
1
5
Order By: Relevance
“…B‐cell receptor (BCR) signalling pathway plays a major role in the growth and survival of mantle cell lymphoma (MCL) cells (Saba et al , ). Inhibition of Bruton tyrosine kinase (BTK) enzyme, a pivotal member of BCR signalling with ibrutinib (Wang et al , ) and acalabrutinib (Wang et al , ) is a major breakthrough in the treatment of patients with MCL. Ibrutinib is commonly used in the treatment of MCL as well as in small lymphocytic lymphoma/chronic lymphocytic leukaemia (SLL/CLL).…”
mentioning
confidence: 99%
“…B‐cell receptor (BCR) signalling pathway plays a major role in the growth and survival of mantle cell lymphoma (MCL) cells (Saba et al , ). Inhibition of Bruton tyrosine kinase (BTK) enzyme, a pivotal member of BCR signalling with ibrutinib (Wang et al , ) and acalabrutinib (Wang et al , ) is a major breakthrough in the treatment of patients with MCL. Ibrutinib is commonly used in the treatment of MCL as well as in small lymphocytic lymphoma/chronic lymphocytic leukaemia (SLL/CLL).…”
mentioning
confidence: 99%
“…However, it does sometimes happen that agents that are more selective might be less effective. Fortunately, a reduction in efficacy with the newer btk inhibitors is not evident, as shown in the acalabrutinib study by Wang et al 14 and the zanubrutinib study by Tam et al 17 , and a reduction in some bothersome aes is even suggested.…”
Section: Q How Do the Novel Btk Inhibitors Attempt To Improve On Ibrumentioning
confidence: 99%
“…To examine the efficacy and safety of acalabrutinib, a highly selective oral inhibitor of btk with minimal offtarget activity, in rr mcl 14,19 .…”
Section: Objectivementioning
confidence: 99%
See 2 more Smart Citations